Factors influencing employee engagement at Petronas twin towers Kuala Lumpur / Mustaffa Munawwar Mustaffa Maarof and Yasirah Jamailudin - Mustaffa Maarof, Mustaffa Munawwar; Jamailudin, Yasirah (Faculty of Business and Management, 2016)
The purpose of this study is to determine the factors that influencing employee engagement at the PETRONAS. It is also to investigate the relationship between the factors like work environment, rewards and career development can influence the employee engagement at PETRONAS Twin Towers Kuala Lumpur. PETRONAS is a leading company in oil and gas industry in Malaysia, therefore it is well known that they have the human capital that contribute to their successfulness. But what matter is whether their employees are engaged towards the job and organization, and what might be the factors to their engagement. This study was using the descriptive study to describe the employees at the PETRONAS Twin Towers Kuala Lumpur. The target population for this study is approximately 20,000 employees who worked at PETRONAS Twin Towers, and the sample size based on the number of populations is 377 employees. Survey questionnaires as a method to collect the data are developed through the adaptation and will be distributed to the sample of the population of the employees at the PETRONAS Twin Towers Kuala Lumpur. SPSS is used to analyse the data in order to get the final result of this research study.